Applying Item Response Theory model for evaluating item and test properties of academic potential test for students with disability - Sukaesi Marianti; Dian Putri Permatasari; Unita Werdi Rahajeng (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
Universitas Brawijaya (UB) is one of the pioneers of inclusive education in higher education in Indonesia. One of the innovations in the policies related to inclusive education is affirmative action admissions special for students with disabilities, namely Seleksi Mandiri Penyandang Disabilitas (Independent Selection for Person with Disabilities), which focuses on accommodating admissions selection for students with disabilities who want to enroll in bachelors or vocational programs. A part of this admission selection is the test called the Computer-Based Academic Potential Test. This study aims to evaluate, from a psychometric perspective, the psychometric properties of the potential academic test. The approach used in this study is the item response theory (IRT) framework, which is mostly used for evaluating psychometric quality at both item-level and test levels. This study's IRT model is a two-parameter logistic model that includes difficulty parameter and discrimination parameter. The result of this study exhibited that the three subtests of the Computer-Based Academic Potential Test, in general, have satisfying results from the 2PL model estimation. The result also showed that most of the item difficulties ranged from medium to very difficult.